Effect of fibrin glue derived from snake venom on the viability of autogenous split-thickness skin graft - Rahal,S.C. (2004)
The aim of this study was to analyze the effect of snake venom derived from fibrin glue on the viability of split-thickness skin graft. Nine crossbreed dogs were used. Full-thickness skin segments measuring 4 x 4 cm were bilaterally excised from the proximal radial area on each dog. A split-thickness skin graft was harvestedfrom left lateral thoracic area using a freehand graft knife, and was secured to the left recipient bed using several simple interrupted sutures of 3-0 nylon (sutured graft). A split-thickness skin graft was harvested from the right lateral thoracic area using a graft knife. Fibrin glue derived from snake venom was applied to the recipient bed, and 8 equidistant simple interrupted sutures of 3-0 nylon were used to secure the skin graft (glued graft). Viable and nonviable areas were traced on a transparent sheet and measured using a Nikon Photomicroscope connected to a KS-300 image analysis system. The skin graft and recipient bed were collected from three dogs at day 7, 15, and 30 postoperative. The glued grafts had statistically higher graft viability than sutured grafts. Histological examination showed that the tissue repair process in the glued grafts was more accentuated than sutured grafts. It was possible to conclude that fibrin glue derived from snake venom increased survival of autogenous split-thickness skin graft.